175PHypermethylation of the PCDHB15 promoter predicts the prognosis in gastric cancer. (24th November 2019) - Lee, Y-T; Hsu, P-Y; Chuang, Y-M; Jin, H; Cheng, A S L; Ng, E K W; Liu, C-J; Chen, Y-C; Cheng, F; Chan, M W Y
Abstract: Background: Helicobacter pylori-induced aberrant JAK/STAT3 signaling contributed to the development of gastric cancer. We hypothesize that activated STAT3 may epigenetically repress it's targets by DNA methylation. The object of this study is to identified the diagnostic and prognostic value of novel STAT3 targets that are hypermethylated in gastric cancer. Methods: Fifty patients' clinical data and genomic DNA were collected from the Changhua Christian Hospital, Taiwan. DNA methylation microarray was used to analyze the methylation status in AGS gastric cancer cells and patient samples with different STAT3 status. Bioinformatic analyses was carried out to identify STAT3 targets with differential methylation status. Bisulphite pyrosequencing was designed and performed in cancer and normal tissue to examine the methylation level of the target genes. Receiver operating character (ROC) curve and the survival analysis were examined. Results: We found that promoter hypomethylation of PCDHB15, a potential STAT3 target, was observed in AGS cells depleted with STAT3, while promoter hypermethylation was observed in patient samples with activated STAT3. Cell line studies found that treatment with the DNMT inhibitor, 5azaDC, restored PCDHB15 expression in AGS. Pyrosequencing in various cell lines, including AGS, MKN28, MKN45, SNU1 and SNU16, demonstrated hypermethylation of the PCDHB15 promoter. Compared to the cancer tissue, a lower PCDHB15 methylation was observed in matched adjacent tissue (P = 0.001) and gastritis tissue (P < 0.001). Interestingly, Kaplain-Meier analysis found that patients with higher PCDHB15 methylation had longer survival as compared to patients with lower methylation (p = 0.03). Conclusions: Our study indicate that methylated PCDHB15 promoter may be associated with development of gastric cancer. Patients with higher PCDHB15 methylation are prone to have better prognosis. Legal entity responsible for the study: The authors. Funding: This study was supported by a grant from Taichung Veterans General Hospital (RVHYCY-107008). Disclosure: All authors have declared no conflicts of interest.